Effects of Nd:Yag Laser on some virulence factor genes of Pseudomonas aeruginosa bacteria - Aidah Abd Al-doori; Awatef Saber Jasem; Adnan F. AL-Azzawie (Tikrit Journal of Pure Science, 2020)
The aim of this study was to assess effects of the 532nm Nd-yag laser on the genes of Tox A, Exo S, and Opr L, of Pseudomonas aeruginosa (P. aeruginosa) bacteria isolated from clinical (wounds, burns, otitis media) and environmental (water, soil) samples. Clinical samples were collected from patients coming to Saladdin General Hospital from wound, burns and middle ear infections while environmental samples were extracted from water and soil for Saladdin General Hospital . Bacterial samples irradiated by Nd-Yag laser with wavelength of 532 nm using energies (300mj,500mj) with (15 and 25 sec) and genomic DNA were extracted from all samples after the diagnosis of P. aeruginosa bacteria depending on the macroscopic and biochemical examination, then the PCR technique was performed. The results have shown an impact on P. aeruginosa bacteria of Nd-Yag laser by comparing PCR results of treated samples with control (unexposed) as loss of normal bands. This indicates that the laser had a genetic effect on the P. aeruginosa bacteria. We conclude that the laser induces genetic changes in P. aeruginosa's DNA so that lasers can be used in treatment and sterilization for clinical and environmental . The PCR technique could be used as a biomarker study to determine the biological effects of radiation on bacteria.